(untitled) (Indian Journal of Animal Production and Management, 2024)
Supernumerary teat (SNT) in cattle, which is the presence of having additional teats, may affect the milk production as well as the management. SNTs can pose a serious problem when it comes to machine or robotic milking. The present work was planned with the objective of studying the presence of SNTs in the Holstein Friesian Crossbred (HFCB) and Jersey Crossbred (JCB) cattle. The results revealed that SNTs were present in 12.27% HFCB and 8.67% JCB cows. The SNTs were either one or two in number, with the incidence of one SNT being higher than the incidence of two SNTs in HFCB cows, whereas the incidence of one and two SNTs were equal (50%) in JCB cows. Overall, the occurrence of one SNT was significantly more in HFCB cows than the JCB cows, whereas the occurrence of two SNTs were significantly more in JCB cows than HFCB cows. The SNTs were found to be located at three different positions viz. anterior, intercalary or caudal location. SNTs were located at intercalary position in 82.35% of HFCB cows, whereas the remaining 17.65% HFCB cows had SNTs located at anterior location. SNTs were located at anterior, intercalary and caudal location in 17.86%, 32.14% and 50% JCB cows.